Diverse One-Pot Electrophilic Trapping Reactions of 2-Quinolylzincates with Acyl Chlorides and Allyl Iodide - Jeong, Hye Jin; Chae, Suyeon; Jeong, Keunhong; Namgoong, Sung Keon (Synthesis, 2020)
The tandem acylation reactions of 2-quinolylzincates under one-pot reaction conditions facilitated the formation of biologically active (Z)-3-alkylidenephthalides and multifunctionalized quinoline derivatives at specific positions. The reactions of these zincates with allyl iodide produced three different types of temperature- and alkyl-ligand-dependent C-2 homologated quinolines. The reaction mechanisms for the formation of the presented products from 2-quinolylzincates are also proposed in detail.
Keywords: 2-quinolylzincate; electrophilic trapping reaction; acylation; multifunctionalization; homologation; isomerization